قصة النبي يوسف عليه السلام وأثرها في السرد الروائي عند فوزي الطائي - أميري، جهانكير; موسى، محمد متعب; معروف، يحيى (الجامعة الإسلامية, 2022)
قصة النبي يوسف عليه السلام ذكرت في القرآن الكريم في سورة يوسف كاملة ولم تتكرر في سور أخرى كما هو الحال مع باقي القصص القرآنية، وهي أحسن القصص، قال تعالى: (نَحْنُ نَقُصُّ عَلَيْكَ أَحْسَنَ الْقَصَصِ بِمَا أَوْحَيْنَا إِلَيْكَ هَذَا الْقُرْآنَ) يوسف: ٣، والكاتب فوزي الطائي شغوف بقراءة القرآن وتدبر معانيه، قد أفاد من وقائع هذه القصة وتأثر بها، من جوانب اللغة والبلاغة والمعاني فوظفها في سرده الروائي فأكسبته حكمة ورشاقة وديباجة مشرقة، وعززت من قناعة القارئ بكتاباته، فضلا عن تأثره بباقي القصص القرآنية وألفاظ القرآن ومعانيه بشكل عام. The story of the Prophet Yusuf (peace be upon him) was mentioned in the Holy Qur’an in Surat Yusuf in full and was not repeated in other surahs as is the case with the rest of the Qur’anic stories, and it is the best of stories, the Almighty said: (We tell you the best stories with what He says) Youssef: 3, and the writer Fawzi Al-Tai is passionate about reading the Qur’an and contemplating its meanings. He benefited from the facts of this story and was influenced by it, from the aspects of language, rhetoric, and meanings, so he employed them in his novelist’s narration. The Qur'an and its meanings in general.
Keywords: الأدب الروائي -- قصص القرآن -- يوسف، عليه السلام -- الأدب العراقي